A Case of anomalous Left circumflex coronary artery - Subedi, B; Ahmed, QA; Arzu, J; Sarker, DK; Sultan, MA; Siddique, MA; Ahmed, MK (University Heart Journal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A 45 years non diabetic, non hypertensive, non smoker presented with chest discomfort that was typical for angina. He had no dyspnoea, syncope, palpitation, family history of coronary artery disease. On examination pulse was 80 beats/min regular, blood pressure 120/70mm of Hg, temperature normal, JVP not raised and physical examination findings were unremarkable. ECG showed the features of inferior wall ischaemia. Echocardigraphic findings were normal with left ventricular ejection fraction of 55%. His lipid profile showed dyslipidaemia with low HDL cholesterol and high LDL cholesterol. Subsequently he underwent coronary angiogram which revealed an ejection fraction of 55%, normal left ventriculography, normal left main artery, 50% stenosis in the proximal part of left anterior descending artery, left circumflex artery having anomalous origin from the proximal part of right coronary artery, Right coronary artery having 90% stenosis at the level of right ventricular branch with irregularities after RV branch and 75% stenosis before its bifurcation into PDA and PLV. Our diagnosis was Single vessel disease with coronary anomaly. Â Â  University Heart Journal Vol.4(1) January 2008